2013
DOI: 10.3109/08037051.2013.823767
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adiponectin: A contributing factor for cardiac changes in visceral obesity-associated hypertension

Abstract: This study has been designed to evaluate the impact of adiponectin levels on left ventricular geometry and function in visceral obesity-associated hypertension. 94 consecutive subjects, 53 of them were hypertensives and 41 normotensives with age ≤ 65 years, subgrouped according to the presence or absence of visceral obesity, were studied. Total adiponectin levels were measured by a validated competitive radioimmunoassay. Left ventricular telediastolic internal diameter, interventricular septum, posterior wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…However, plasma adiponectin levels are low in subjects with visceral fat accumulation and it seems to play an important role in the pathogenesis of visceral fat syndrome [1][2][3]. Our previous data [4] and some clinical studies reported an inverse association between ADPN and left ventricular mass (LVM) [1,5]. Moreover, increased ADPN expression can attenuate left ventricular hypertrophy (LVH) induced by pathological stimuli and it is able to protect the ischemic heart from injury, through the activation of independent pathways [1,2,4,5].…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…However, plasma adiponectin levels are low in subjects with visceral fat accumulation and it seems to play an important role in the pathogenesis of visceral fat syndrome [1][2][3]. Our previous data [4] and some clinical studies reported an inverse association between ADPN and left ventricular mass (LVM) [1,5]. Moreover, increased ADPN expression can attenuate left ventricular hypertrophy (LVH) induced by pathological stimuli and it is able to protect the ischemic heart from injury, through the activation of independent pathways [1,2,4,5].…”
Section: Introductionmentioning
confidence: 77%
“…The concentration of ADPN was obtained by a radioimmunoassay using a human ADPN RIA kit (LINCO Research, Inc., Billerica, MA, USA) as previously described [4]. Patients with and without MetS were further subdivided in four groups, according to level of ADPN, higher than or equal to 6 µg/mL (normal ADPN groups) and less than 6 µg/mL (low ADPN groups) ( Table 1).…”
Section: Biochemical Measurementsmentioning
confidence: 99%
See 3 more Smart Citations